Application of time-series-cross-section data in the case of forecasting sale in an enterprise - Sobiechowska-Ziegert, Aneta (Wykorzystanie danych przestrzenno-czasowych do prognozowania sprzedaży w przedsiębiorstwie - przykład rynku paliw płynnych, 2011)
The article treats possibilities of using time-series-cross-section data for sales forecasting in an enterprise. Different kind of approaches to econometric forecasting using TSCS data are presented. Short-run forecasts of gasoline sales according to regions in Poland are determined and their quality with the use of the ex-post measures is estimated. The most accurate forecasting methods are then used to create a combined forecast. In the summary. advantages and disadvantages of the particular approaches are indicated as well as the conditions of their practical use.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 20-38
Keywords: prognozowanie; sprzedaż; rynek paliw; prognozowanie sprzedaży; forecasting; sale; fuel market; sales forecasting